EVALUASI SISTEM DAN PROSEDUR PEMBENTUKAN SERTA PENGGUNAAN UANG PERSEDIAAN PADA KANTOR BAPELITBANGDA KOTA MANADO - Pido, Yurike Sella; Tinangon, Jantje J; Pinatik, Sherly (Universitas Sam Ratulangi, 2017)
Inventory money is cash in hand of expense treasurer, this fund is given once in one budget year and is revolving. The amount of Inventory Money depends on local policy. Systems and Procedures used in the Establishment and Use of Inventory Money need to be assessed so it can be known whether it is in accordance with Permendagri No.13 / 2006 which then revised to Permendagri No.21 / 2011 on Management of Regional Financial Guidance. The purpose of this study is to evaluate whether the System and Procedure of Establishment and Use of Inventory at the BAPELITBANGDA office of Manado city is in accordance with the applicable Regulations. The research method used is descriptive which gives a systematic, factual, accurate description of the problem under investigation. The result of the research shows that BAPELITBANGDA Manado has implemented System and Procedure effectively in accordance with Permendagri No .13 / 2006 and the second amendment of Permendagri No.21/2011Keywords: funds inventory money, systems and procedures, evaluation